Education on Preventing Verbal and Digital Violence in Islamic Boarding Schools: A Persuasive Approach - Sunardi Sunardi; Moh. Kholik; Isah Munfarida; Rusdee Waenasae (An Naf'ah: Jurnal Pengabdian Masyarakat, 2026)
Al-Urwatul Wutsqo Islamic Boarding School (Pesantren) faces serious challenges regarding normalized verbal bullying (gojlogan) and the risk of cyberbullying among its Junior (MTs) and Senior (SMA) High School students, particularly amidst the inevitable expansion of the digital era. This community service program aimed to enhance understanding and cultivate a commitment to non-violence within the pesantren environment through a Persuasive-Educative Approach. The implementation method involved preliminary observations and interactive education utilizing empathy simulations, alongside the integration of Ukhuwah Islamiyah (Islamic Brotherhood) values and legal awareness regarding the Electronic Information and Transactions (ITE) Law. The results indicated a significant increase in student awareness concerning the psychological impacts of bullying and the legal consequences of digital violence. The persuasive approach proved highly effective in fostering empathy, prompting self-reflection (muhasabah), and successfully mobilizing a collective commitment against bullying among participants, as documented in a joint declaration. It is concluded that this method serves as a humanistic, valid, and highly relevant preventive solution for the pesantren context, which is characterized by intense social interaction and a transition toward digital culture